Developing the socioculture-based thematic-integrative learning module for improving the learning motivation and the critical thinking - Sulistiya Ingwarni (Jurnal Prima Edukasia, 2018)
This study aims to (1) produce thematic integrative learning modules based on sociocultural background feasible to increase student’s learning motivation and critical thinking, and (2) determine the effectiveness of the integrative thematic learning module. This research was included in the type of research and development (R D). Development procedures in this study adapting development procedures developed by Borg and Gall with steps, namely: (1) a preliminary study, (2) planning, (3) the design of the product, (3) field trials beginning, (5) the revision of the results of the initial field trials, (6) the main field trials, (7) the revision of the main results of field trials, (8) operational field trials, (9) the improvement of the final product. The subjects of the trial are fourth-grade students Jejeran, Bantul. The results show that (1) the integrative thematic learning module based on sociocultural background feasible according to media experts and subject matter experts with category ratings "very good". (2) The integrative thematic learning modules based on the sociocultural background is effective to improve student’s learning motivation and critical thinking. It is based on the results obtained by operational field trials p 0.05, which means that there are significant differences on motivation to learn and critical thinking of students who take the learning of the module and who do not use the learning module.